An essay about the effect of vague accounting standards on the decision making process of auditors - Nishi, Heather (2010)
Vague words and expressions are present throughout the standards that comprise the accounting and auditing professions. Vagueness is considered to be a significant source of inexactness in many accounting decision problems and many authors have argued that the neglect of this issue may cause accounting information to be less useful. On the other hand, we can assume that the use of vague terms in accounting standards is inherent to principle based standards (different from rule based standards) and that to avoid vague terms, standard setters would have to incur excessive transaction costs. Auditors are required to exercise their own professional judgment throughout the audit process and it has been argued that the inherent vagueness in accounting standards may influence their decision making processes. The main objective of this paper is to analyze the decision making process of auditors and to investigate whether vague accounting standards create a problem for the decision making process of auditors, or lead to a better outcome. This paper makes the argument that vague standards prompt the use of System 2 type processing by auditors, allowing more comprehensive analytical thinking; therefore, reducing the biases associated with System 1 heuristic processing. If our argument is valid, the repercussions of vague accounting standards are not as negative as presented in previous literature, instead they are positive.